Cross-country skiing physical training pattern for the 10 km classic event - Balint, G.; Lungociu, l. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Considering the achievements of the Romanian sportsmen during the great competitions, the Olympic Games and the World Championships, where they have achieved average results, although the time difference compared to the winners has decreased considerably, we have suggested, by means of this paper, an improvement of the training plans for the performance cross-country skiers who are included in the Romanian Olympic team.